Calibração do coeficiente de decaimento do cloro (Kw) em redes de abastecimento de água utilizando o método iterativo do gradiente hidráulico alternativo (MIGHA) - Pereira, Rejane Félix (2009)
One of the biggest challenges of the Brazilian companies to sanitation is the provision of drinking water within the quality standards recommended by the Ordinance No 518/2004 of the Ministry of Health. To obtain this quality, it is common practice to use chlorine in water treatment plants. However, it participates in various reactions with the compounds of organic and inorganic nature on the inside of pipes, reacting both within the liquid, as the walls of the pipes, causing the decay of chlorine throughout the distribution network. Considering the above, to make more efficient the management of residual chlorine in water distribution systems, the literature describes the use of modeling, assuming that the effects of the decay of chlorine can be represented by the coefficients kbulk and kwall. However, the calculation of these parameters is a complex task, because the systems have different types of piping materials, variation of age of the pipes that make up and the types of springs (surface and underground) entered in the system. In this work, it developed a computational routine to determine the parameter of decay of chlorine in the walls of the pipes (kwall) in distribution networks for drinking water, using the Iterative Method of Hydraulic Gradient Alternative (MIGHA) as a method of optimization. The proposed calibration model was applied to a network model, with results evaluated according to the number of nodes with residual chlorine concentrations of the known. In order to compare the results, the proposed model was also applied to a hypothetical network studied in other works whose determination of the parameter in question was performed by the method of genetic algorithms